Range, Plateau and Coast: Foot and Water Traces - Marín, Marcela Cecilia (2023)
In a context of intense conflict in the province of Chubut, Argentina, in the face of the threat, once again, of allowing mining zoning, this essay takes up again some of those marches and walks of a resistance that has been sustained for more than 18 years. From the slogan "#ChubutAGUAzo" "one people, one river", which arose in 2020 during ASPO/DISPO, in the context of a new onslaught against the prohibition of mining activity established in Law 5001 and the First and Second Popular Initiative, our proposal goes back to another experience of struggle, starting from these firefly walks, small traces of feet, words and dust that crossed, as the Chubut River does, mountain range, plateau and coast in defense of life, against the terricide. Our writing tries to trace back the writings that cross that mountain, plateau and coast. We try to bring closer the drawing marked by some firefly feet in the " Marcha de los Poetas y Artistas" and the drawing traced by the Chubut river in its course: feet and waters move the remains of other struggles.